The illusion of deterrence : the Roosevelt presidency and the origins of the Pacific war - Ben-zvi, Abraham (Boulder : Westview, 1987)
Roosevelt, Franklin Delano, 1882-1945
Keywords: U.S. -- Foreign relations -- Japan; Japan -- Foreign relations -- U.S..; United States -- Foreign relations